Stephen Krashen: His contributions to bilingual education - Contreras Salas, Olga Lucía (Rastros Rostros, 2012)
The following article is an approach to the life and work of Linguist Stephen Krashen.This section of “Great Biographies” is dedicated to this professor because of his contributions to the Second Language Acquisition theory for bilingual education. Also, we present this author because his work is coherent with the dossier of this publication. The essence of Krashen’s Second Language Acquisition theory states that real acquisition does not happen overnight; it is a slow process in which speaking skills emerge from listening skills through a long period of time.